MANAGEMENT MODEL AND ITS APPLICATION IN SMALL AND MEDIUM ACCOMMODATION COMPANIES - Miño Freire, María Fernanda; Echeverría Benalcázar, Ronny Santiago (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019DO - 10.36779/mktdescubre/v#.#, 2020)
The model was designed based on information obtained through interviews with the managers of accommodation Small and Medium Enterprises (SMEs) in the city of Riobamba. The model consists of identifying the need of adapted planning tools, a process design, a guide of the minimum skills required by personnel and an adequate procedure for the design and management of a Marketing Plan, as most the current management practices are empirical and not documented. This research is a practical guide with matrices of processes and activities carried out in thirteen positions, which were identified by their performance competences before, during and after exercising the position. In addition, a marketing plan was designed to attract customers, establish alliances, position the image and improve management in Small and Medium-sized accommodation companies.